O uso de hortas nas escolas: percepções da comunidade escolar de Santa Luzia do Pará - MOREIRA, Maria Aldenora Farias (2024)
The school garden is an activity that provides a variety of benefits for science teaching, addressing environmental issues, healthy eating and in an interdisciplinary way, themes that are extremely relevant to contemporary schools. The general objective was to investigate the practice of multidisciplinary actions related to the cultivation of vegetable gardens in municipal schools in Santa Luzia do Pará, state of Pará. This is qualitative research, of the field research type. We chose as a data collection instrument a semi-structured questionnaire aimed at members of the school teaching staff of two schools in the city of Santa Luzia do Pará. The questionnaires sought to determine how directors, coordinators and teachers relate to the use of gardens in schools, in addition to their assessment of the main obstacles to implementing them. As a result, we observed that professionals reported the need for a specific professional for the permanent maintenance of the garden, as well as the lack of material and financial support as one of the obstacles to implementing school gardens. We therefore emphasize the importance of the partnership between municipal management and school management in the implementation of projects aimed at the permanent practice of school gardens. We believe that this work can contribute to future research involving pedagogical interventions such as the execution of school garden projects, contributing to the local school community.